Malaysian English: can or not? - Abu Sufi, Mohd. Khairul; Yaakob, Nor Hasni; Abdul Razak, Azura (Kaizentrenovation Sdn. Bhd., 2020)
Mangled English or Manglish which is a variety of English that is typically Malaysian and spoken widely in Malaysia and Singapore, is a topic which is much discussed and debated on in regard to the advantages and disadvantages of its use. Not only is it disseminated across various domains, it is also said to perform numerous contributory and integrative functions alongside other languages within the country. It is a communicational tool for a significant segment of the multi-ethnic and plays a central role in the lives of locals across Malaysia. Even so, there exist advantages and disadvantages on its usage. This paper strives to objectively outline the benefits and drawbacks of using Malaysian English or Manglish.